Korelasi Historisitas Ilmu Hisab Rukyat Dengan Perkembangan Peradaban Islam - Li'izza Diana Manzil (AL-ISTINBATH : Jurnal Hukum Islam, 2018)
Few people, especially the layman who understands that the science of reckoning and rukyat can also be called as the science of falak (islamic astronomy). This is caused in the implementation of islamic astronomy science found manythe practice of reckoning (calculation) and rukyat (observation). If you look a few years ago, the practice of hisab rukyat has been implemented by Rasulullah SAW even before Islam came. In history noted the development of the science of hisab rukyat experienced rapid development in the Islamic world. it proven from the birth of a number of intellectual Muslim who are proficient in the astronomy, astrology, mathematics and other exact science. In addition, the number of writings and instruments created can not be denied Islamic civilization continues to experience the golden age. From this, it clearly shows the historicity of the science of hisab has an important correlation to Islamic civilization, such as in the calculations and studies of sky object for the practice of Falak Science experience the level of carefulness more accurate. So rapid the science of hisab rukyat science from the era of the Prophet until the modern era shows that Islamic civilization also experienced rapid development along the course of history.